Символика зеркала в лирике Вяч. Иванова и романе В. Набокова «Дар» - Комяти, Диана (SlavVaria, 2026)
The Symbolism of the Mirror in the Lyric Poetry of Vyacheslav Ivanov and in Vladimir Nabokov’s Novel The Gift. In Nabokov’s work, the motif of the mirror functions as a stable and semantically rich image. At the same time, its core meanings, as we see it, are correlated with the categories of vertical and horizontal orientation and resonate with the early poetry of Vyacheslav Ivanov. The mirror placed in a horizontal plane and directed toward the human subject symbolizes the closed nature of subjective perception and generates an infinite series of doubles; the vertically oriented mirror, by contrast, is associated with the spiritual dimension of existence. This opposition first emerges in Nabokov’s early poem The Mirror, and is further developed in the novel The Gift, where the mirror motif also becomes entwined with the theme of artistic creation.